Deciphering the subaltern terrain : exploring Dalit and tribal religio-cultural spaces for an emancipatory vision - Massey, James, 1943-; South Asia Theological Research Institute (Bangalore, India); Serampore College. Committee for Ecumenical Relations and Church Ministries (Bangalore : BTESSC/SATHRI, 2009)
Transcript of papers presented at two regional consultations organized by the Committee for Ecumenical Relations and Church Ministries (CERCM) and the Board of Theological Education of the Senate of Serampore College (BTESSC), held at Hyderabad during 28-30 November 2008 and at New Delhi during 2-4 December 2008.
pt. 1. Devotions -- pt. 2. Three addresses -- pt. 3. Presentations -- pt. 4. Reports.
Includes bibliographical references.
Keywords: Dalits -- India -- Social conditions -- Congresses; Dalits -- India -- Religion -- Congresses; India -- Scheduled tribes -- Religion -- Congresses; Tribes -- India -- Religion -- Congresses; Liberty -- Religious aspects -- Christianity -- Congresses